Successful Pregnancy in a Patient with Crohn’s Disease and Short Bowel Syndrome: Off Total Parenteral Nutrition and On Teduglutide, a Glucagon-Like Peptide-2 Analog – A Case Report - Maria M. Dahar; MacKenzie Both; Linda M. Lord; Carly Densmore; Lawrence J. Saubermann (Case Reports in Gastroenterology)
Introduction: Patients with short bowel syndrome (SBS) on conventional oral diets often face nutritional deficiencies and dehydration, a challenge further compounded during pregnancy. This case report describes the use of a glucagon-like peptide-2 (GLP-2) analog in the nutritional management of an SBS patient dependent on total parenteral nutrition (TPN). Case Presentation: A 29-year-old woman with a significant medical history of Crohn’s disease leading to SBS was traditionally dependent on TPN for sustenance. During her pregnancy, she was successfully managed with a GLP-2 analog, which enabled her to wean off TPN. This successful management underscores the therapeutic potential of GLP-2 analogs in effectively altering the nutritional landscape for SBS patients, including during the physiologically demanding period of pregnancy. Conclusion: GLP-2 analogs helped with the nutritional management of patients with SBS during pregnancy and helped them wean off TPN. There is a need for further research and exploration into GLP-2 analogs as viable alternatives to conventional treatments such as TPN in the care and management of SBS patients during pregnancy.